FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN MEMBAYAR PAJAK (Survei pada Profesi Dokter di Wilayah Kabupaten Sragen) - Eva Putri Oktaviani Aris Eddy Sarwono (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2014)
The purpose of this study was to analyze the significance of the influence of consciousness pay taxes, tax knowledge, understanding of tax laws, the perception of the effectiveness of the tax system and the quality of service taxation partially or simultaneously to the willingness to pay taxes on the medical profession in PHC Sragen. This study used a survey approach to the medical profession in PHC Sragen. The population in this study were all general practitioners in the health center profession Sragen which amounted to 79 people, the sampling technique using quota sampling based on the number of questionnaires returned, as many as 67 respondents. Output coefficients were obtained conclusion: Variable consciousness pay taxes, knowledge of taxation, understanding tax regulations, the perception of the effectiveness of the tax system, and quality of service tax partially positive and significant effect on the willingness to pay taxes) in the medical profession in the health center which Sragen. The contribution of independent variables namely consciousness pay taxes), knowledge of taxation, understanding tax regulations, the perception of the effectiveness of the tax system, and quality of service tax on the dependent variable, namely the willingness to pay taxes in the medical profession in the health center Sragen by 90,5 percent. Keywords: consciousness pay taxes, knowledge of taxation, understanding tax regulations, the perception of the effectiveness of the tax system